Budget impact analysis of venetoclax for the management of acute myeloid leukemia from the perspective of the social security and the private sector in Argentina. - Alfredo Palacios; Natalia Espinola; Juan Martin Gonzalez; Carlos Rojas-Roque; Maria Marta Rivas; Diego Kanevski; Pierre Morisset; Federico Augustovski; Andres Pichon-Riviere; Ariel Bardach (PLoS ONE, 2024)
Objective This study aimed to estimate the budget impact of the incorporation of venetoclax for the treatment of patients with Acute Myeloid Leukemia (AML) over 75 years of age or those with comorbidities and contraindications for the use of intensive chemotherapy, from the perspective of the social security and the private third-party payers in Argentina. Methods A budget impact model was adapted to estimate the cost difference between the current scenario (azacitidine, decitabine and low doses of cytarabine) and the new scenario (incorporation of venetoclax) for a third-party payer over a time horizon of three years. Input parameters were obtained from a literature review, validated or complemented by expert opinion using a modified Panel Delphi approach. All direct medical costs were estimated by the micro-costing approach and were expressed in US dollars (USD) as of September 2020 (1 USD = 76.18 Argentine pesos). Results For a third-party payer with a cohort of 1,000,000 individuals covered, incorporating venetoclax was associated with an average budget impact per-member per-month (PMPM) of $0.11 USD for the social security sector and $0.07 USD for the private sector. The duration of treatment with venetoclax was the most influential parameter in the budget impact results. Conclusion The introduction of venetoclax was associated with a positive and slight budget impact. These findings are informative to support policy decisions aimed to expand the current treatment landscape of AML.